2022
DOI: 10.1186/s40623-022-01657-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal influence of sea level on inland stress based on seismic velocity monitoring

Abstract: Earth’s crust responds to perturbations from various environmental factors. To evaluate this response, seismic velocity changes offer an indirect diagnostic, especially where velocity can be monitored on an ongoing basis from ambient seismic noise. Investigating the connection between the seismic velocity changes and external perturbations could be useful for characterizing dynamic activities in the crust. The seismic velocity is known to be sensitive to variations in meteorological signals such as temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Other studies (Andajani et al, 2022;Kramer et al, 2023) suggest that in saturated conditions (e.g., at the seafloor), when cracks close from increasing stress, the fluid within is pushed to the pores, which leads to an overall increase of the pore pressure and a decrease of seismic velocity. In addition, a phase delay of seismic velocity changes relative to the applied strain also has been observed by previous studies (Sens-Schönfelder & Eulenfeld, 2019;Takano & Nishida, 2023).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Other studies (Andajani et al, 2022;Kramer et al, 2023) suggest that in saturated conditions (e.g., at the seafloor), when cracks close from increasing stress, the fluid within is pushed to the pores, which leads to an overall increase of the pore pressure and a decrease of seismic velocity. In addition, a phase delay of seismic velocity changes relative to the applied strain also has been observed by previous studies (Sens-Schönfelder & Eulenfeld, 2019;Takano & Nishida, 2023).…”
Section: Discussionmentioning
confidence: 96%
“…As a result of insitu stress changes induced by loading, cracks may close when oriented horizontally and open when oriented vertically. Therefore local heterogeneities (Andajani et al, 2022) in the seafloor could be the reason for the observed polarity oscillation in the space (Figure 8). We also acknowledge that some of the anomalies could be seismic inversion artifacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…at the seafloor), when cracks close from increasing stress, the fluid within is pushed to the pores, which leads to an overall increase of the pore pressure and a decrease of seismic velocity. Furthermore, Andajani et al (2022) found that the correlation between sea level height and nearby inland seismic velocity changes can be negative or positive, depending on the in-situ local stress, orientation of dominant crack, and hydraulic conductivity. The local heterogeneities (Andajani et al, 2022) in the seafloor could also be the reason for the observed negative anomalies in the time-lapse seafloor images (Figure 7) associated with positive velocity changes and the positive anomalies in the images corresponding to negative velocity changes, although we acknowledge that some of the anomalies could also beyond the resolution of seismic inversion.…”
Section: Discussionmentioning
confidence: 99%
“…We can use the information from the cross-correlation functions (CCFs) of coda waves (i.e., the scattered waves in the subsurface due to crustal heterogeneities) to obtain stable estimates of the velocity changes (e.g., Meier et al, 2010;Sens-Schönfelder & Wegler, 2006). The ambient noise-derived monitoring data can provide continuous information that is relevant to volcanic activity because the observed velocity changes are related to the crustal stress state, pore pressure changes, crack generation, and/or the presence of volcanic and hydrothermal fluids (Andajani et al, 2020(Andajani et al, , 2022Brenguier et al, 2014;Wang et al, 2017). However, most studies of ambient noise monitoring have used a longer period of data (i.e., longer data window) for the velocity monitoring, such that the monitoring results generally possess a lower temporal resolution (e.g., several to 10 days; Hutapea et al, 2020).…”
Section: Introductionmentioning
confidence: 99%